SŪRYA DALAM PRATIṢṬHĀ DAN RASAVYAÑJAKA: HERMENEUTIK BHĪṢMA DALAM KAKAVIN AMBŚRAYA MENURUT TEORI DHVANI ĀNANDVARDHANA - Manu J. Widyaseputra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
This article explores the existence of Bhīṣma in theAmbâśraya Kakavin with applying the Dhvani theory ofĀnandavardhana in his book Dhvanyāloka. Dhvani isbasically a hint, a silent suggestion, and works merethrough evocation than through implication. Whatever isimplied can be arrived at merely from an analysis of theimplying statement or gesture. Not so with dhvani. Noamount of analysis can be lay bare the dhvani-effect, ifthe hearer/reader does not have a special qaulity thatattunes him to it. Whereas an implication can be pin-pointed, and even expressed, dhvani can never be pin-pointed, much less can it be expressed in words. It can atbest be merely pointed at through figures speech of OldJavanese kakavin but its precise content evadesformulation.